Prenatal „indywidualized growth curve standards” and errors in fetal conceptual age assessment - Sawicki, Konstanty (Anthropological Review, 1995)
The paper presents some important, but as yet insufficiently solved, methodological problems of anatomical and ultrasound fetal growth research.